O Trenzinho Caipira: narrativa reflexiva da minha vivência no curso - Brito, Iago Júlio Fernandes Nogueira (Universidade Federal de São Carlos, 2023)
Reflective narrative work, presented as Course Conclusion Work, discussing the individual experiences of the student during the training in medical degree at the Federal University of São Carlos. The paper discusses the individual construction of the student during his years of formation, using cultural and identity perspectives of the student.
The Caipira Train: Reflective narrative of my experience in the course
Keywords: Formação; Medicina; São Carlos; Construção; Identidade; O Trenzinho Caipira; Training; Medicine; Construction; Identity; The Caipira Train; CIENCIAS DA SAUDE::MEDICINA